Lateralized hippocampal oscillations underlie distinct aspects of human spatial memory and navigation - Jonathan Miller (Nature Portfolio, 2018)
Theta oscillations are implicated in memory formation. Here, the authors show that low-theta oscillations in the hippocampus are differentially modulated between each hemisphere, with oscillations in the left increasing when successfully learning object–location pairs and in the right during spatial navigation.